THE IMPLEMENTATION OF SHARIA-BASED CREATIVE ECONOMY THROUGH GOOD GOVERNANCE TO ACHIEVE THE REGIONAL INDEPENDENCE LEVEL - Zulkarnaini; Dasmi Husin; Mukhlisul Muzahid; Ali Imran; Anhar Firdaus; Lakharis Inuzula (CV. Radja Publika, 2023)
The right to regional autonomy is a source of strength for local governments in realizing community prosperity. Therefore, a work program is needed that can encourage the acceleration of regional progress so that the region can achieve the level of regional independence. The purpose of the study is to recommend local governments, especially the Lhokseumawe City Government, to be able to increase the potential of the region through the application of a sharia-based creative economy that is very in line with local culture.The target of this research is the independent variable, namely the application of sharia-based creative economy and good governance, while the dependent variable is the level of regional independence. This research is a survey of government officials. The analytical tool used is Moderated Regression Analysis (MRA). The intended respondents are people who are involved in the upper-middle management level, or who are directly involved in the operational processes of the government based on established criteria (purposive sampling).The results show that the application of a sharia-based creative economy has a significant influence on the level of regional independence in the Lhokseumawe City Government, while the application of a sharia-based creative economy moderated by good governance also has a significant influence on the level of regional independence. In other words, good governance can strengthen the influence of the application of a sharia-based creative economy on the level of regional independence.